2004
DOI: 10.1111/j.1600-6143.2004.00488.x
|View full text |Cite
|
Sign up to set email alerts
|

Creatinine Reduction Ratio on Post-Transplant Day Two as Criterion in Defining Delayed Graft Function

Abstract: Delayed graft function (DGF) is a common complication after renal transplant, affecting its outcome. A common definition of DGF is the need for dialysis within the first week of transplantation, but this criterion has its drawbacks. We tried to validate an earlier and better defined parameter of DGF based on the creatinine reduction ratio on post-transplant day 2 (CRR2).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
1
7

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(62 citation statements)
references
References 32 publications
1
53
1
7
Order By: Relevance
“…Early allograft dysfunction was defined in two ways: serum creatinine greater than 265 umol/L with or without hemodialysis on day 7 posttransplantation (30,31); or the need for dialysis within the first week after transplantation (the usual definition of DGF (30,32). The study investigators were not involved in the decision to initiate dialysis.…”
Section: Clinical Assessment Of Kidney Allograftsmentioning
confidence: 99%
“…Early allograft dysfunction was defined in two ways: serum creatinine greater than 265 umol/L with or without hemodialysis on day 7 posttransplantation (30,31); or the need for dialysis within the first week after transplantation (the usual definition of DGF (30,32). The study investigators were not involved in the decision to initiate dialysis.…”
Section: Clinical Assessment Of Kidney Allograftsmentioning
confidence: 99%
“…10 Even in patients not dialyzed after transplant, studies have shown poorer long-term outcomes with "slow graft function (SGF)" compared with "immediate graft function (IGF)." 3,11,12 Although most studies agree that DGF is associated with poorer outcomes, multiple DGF definitions are used. [13][14][15][16][17] Current means of diagnosing DGF or SGF, using Scr and urine output (UOP), require knowledge of previous values to interpret, are affected by diuretic use, and can take a number of days to confirm.…”
mentioning
confidence: 99%
“…Las complicaciones médicas no infecciosas más comúnmente halladas fueron la NTA, las crisis hipertensivas, el EAP y las arritmias. En el caso particular de la NTA es la complicación médica más frecuente en la casi absoluta totalidad de las series de pacientes de TR [14][15][16] . En nuestro caso, si consideramos que habitualmente trasplantamos con tiempos de isquemia fría superiores a las 20 horas, no es de asombrarse estos resultados, pues es conocido que el tiempo de isquemia es un factor de riesgo muy importante para el desarrollo de NTA 13, 17, 18 .…”
Section: Discussionunclassified